Understanding the Dictatorship of the Proletariat: The Canadian Left and the Moment of Socialist Possibility in 1919 - Campbell, Peter (Labour / Le Travail, 2009)
Abstract The Canadian labour revolt was about more than wages and working conditions. The year 1919 was also a moment of socialist possibility in which the Russian Revolution and the influence of Marx and Engels fuelled the revolutionary intent of a radicalizing Canadian working class. The idea of the dictatorship of the proletariat, long since lost in the shadow of Stalin’s terror, fuelled this moment of socialist possibility. The longing for a workers’ state was a nation-wide phenomenon, but it manifested itself more deeply and broadly in western Canada than in the east. West of the Great Lakes, the concept of the dictatorship of the proletariat was hotly debated in the pages of socialist papers and in the halls of the labour movement. Knowledge of the debate concerning the dictatorship of the proletariat provides a more complete understanding of the labour revolt of 1919 and its legacy for Canadian history and the international left.